A rare comorbidity: neurosarcoidosis and cutaneous sarcoidosis. (17th November 2015) - Akyol, Lütfi; Aslan, Kerim; Özgen, Metin; Sayarlioglu, Mehmet
Abstract : We present a case of a neurosarcoidosis patient with skin lesions. A 50-year-old woman was admitted with a 1-year history of violaceous, smooth and shiny plaques on her face and right arm. These lesions were biopsied and the histological examination indicated sarcoidosis. The patient had a history of headache and syncope that lasted for about 1 h. Brain CT showed masses measuring 37×20 mm in both frontal lobes. Thoracic and abdominal CT showed many pathologically enlarged lymph nodes. The patient was diagnosed with cutaneous, lung and neuronal sarcoidosis, and treated with 20 mg/day methylprednisolone, 15 mg/week methotrexate, 10 mg/week folic acid, 400 mg/day hydroxychloroquine and 800 mg/day carbamazepine. One month later, the patient's neurological symptoms had improved and her skin lesions had decreased. At 6-month follow-up, the size of the cranial masses had markedly regressed.